Dysfunctions of NPOs and NGOs in Poland in the Global Context: Some International Comparisons - Janusz Fudaliński (Entrepreneurial Business and Economics Review)
The purpose of the article is an initial diagnosis of the level of internationalization and globalization of non-profit organization sector in Poland, as well as indication of possible differences in this respect, reflected in selected well-developed countries.